Determinants of Health Tourism Destination Attractiveness: A Comprehensive Systematic Review - Mandagi, Deske W.; Tappy, Yunita Peggy (Penerbit Goodwood, 2024)
Purpose: This study aims to acquire a comprehensive understanding of the factors contributing to the attractiveness of medical tourism destinations (MTD). Method: Utilizing a systematic literature review (SLR) methodology, this research conducts an in-depth analysis of academic journal articles published between 2010 and 2024, indexed in the Scopus database. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method serves as the framework for this systematic review, ensuring the robustness of the review process through meticulous screening, data extraction, and synthesis of findings. Result: The results reveal four prominent factors determining medical tourism attractiveness. First, economic factors such as the cost of medical expenditures, destination competitiveness, and economic diversification. Second, cultural and social factors including destination attributes, tourism and vacation experience and geographical distance. Third, healthcare infrastructure and quality standards, encompassing service quality factors, medical treatment quality and government support for medical tourism infrastructure. Fourth, and lastly, marketing and promotional strategies, including branding, marketing, and destination perception. This comprehensive analysis provides valuable insights for stakeholders aiming to enhance the appeal of medical tourism destinations.